Cost and Time Analysis of the Acceleration Earthworks with the Method of Adding Heavy Equipment to the Depok-Antasari Toll Road Project - Irriene Indah Susanti; Fahmizan Rimawan (Yayasan Ahmar Cendekia Indonesia, 2021)
The development of Depok-Antasari Toll road construction was delayed by the work on the implementation of land work of 30.70% from the original plan presentation so that The initially planned time was completed in August 2019 extended to be completed in December 2019. In this study will analyze the acceleration of completion duration on The construction project of Depok–Antasari Toll road with an alternative to the number of heavy equipment. The purpose of this research is to know the cost of project that is physical and duration of time is faster by using the alternative. The results of the analysis was obtained that total project cost under normal conditions is IDR. 9,860,552,249.00 with the duration of project execution 130 working days. In the condition after accelerated with the addition of the number of heavy equipment alternative– 1 obtained a fee of Rp. 10,030,638,486.00 or more expensive 1.02% of the project cost in normal conditions and duration Project execution of 109 business days or faster 21 days from the normal duration. While the total cost of the project in the alternative condition–2 obtained Rp. 10,153,918,103.00 or more expensive 1.04% of the project cost under normal conditions and duration of project execution 104 days or faster 26 days from the normal duration. It can concluded that the acceleration of work by alternative method-1 is a more effective and economical acceleration alternative, because By applying an alternate acceleration–1. The duration of project work is faster than normal circumstances and does not experience a delay of employment from the planned time of 120 days. And the total budget cost of the project is cheaper compared to the alternative acceleration method-2.